Identification of biomarkers for tumor regression grade in esophageal squamous cell carcinoma patients after neoadjuvant chemoradiotherapy - Chen, Zhifu; Wang, Yan; Chen, Jun; Xu, Zijun; Zhang, Tingjuan; Sun, Lu; Zhu, Lihua; Xu, Liben; Wu, Chaoyang; Qiu, Zhiyuan; Wang, Dianjun; Wu, Ting (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer is a highly invasive malignancy. Neoadjuvant chemoradiotherapy not only increases the rate of complete resection but also improves the median survival. However, a sensitive biomarker is urgently needed in clinical practice.Methods60 esophageal squamous cell carcinoma (ESCC) patients undergoing neoadjuvant chemoradiotherapy (NCRT) were enrolled at the People's Hospital Affiliated to Jiangsu University. Patients were grouped according to tumor regression grade (TRG) criteria from the College of American Pathologists (CAP). The correlation between TRG groups, clinicopathologic characteristics, and prognosis was analyzed. Differential gene expression analysis was performed on ESCC patients before and after NCRT using the public database (GSE43519). MMP9, NFIX, and GPR56 were identified as candidate genes, and their expression and correlation with prognosis were evaluated by immunohistochemical analysis.ResultsAmong 60 ESCC patients who underwent surgery after NCRT, the pathological complete response (pCR) rate was 35.0% (21/60), and the major pathological response (MPR) rate was 60.0% (36/60). Poor tumor differentiation and neural or vascular invasion were associated with inadequate tumor regression grade and were independent factors influencing TRG. ESCC patients were divided into effective (TRG 0 + 1) and ineffective (TRG 2 + 3) groups. Higher TRG was significantly associated with shorter overall survival (OS). Our study also identified TRG as an independent prognostic factor through univariate and multivariate Cox regression analyses (P < 0.05). The differentially expressed genes GPR56, MMP9, and NFIX selected from the GSE43519 dataset were significantly downregulated after NCRT (P < 0.001). Immunohistochemistry showed that GPR56 was highly expressed in ESCC, while it was negatively expressed in paracancerous tissues. There was a significant difference in expression between cancerous and paracancerous tissues. GPR56 expression was consistent with the public dataset, and patients with high GPR56 expression had significantly shorter OS (P < 0.05). In addition, patients with inadequate MPR and high GPR56 expression had shorter OS (P < 0.05).ConclusionsThe findings suggest that TRG serves as an independent prognostic factor for ESCC following NCRT. High GPR56 expression is found to be associated with a poor prognosis of ESCC. Downregulation of GPR56 suggests a potential significant predictive value in conjunction with MPR analysis.